2018
DOI: 10.31021/jcro.20181107
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Of Cancer Treatment Through Overcoming Drug Resistance

Abstract: Cancer Drug resistance is a medical concern that requires extensive research and a thorough understanding in order to overcome. Remarkable achievements related to this field have been accomplished and further work is needed in order to optimize the cure for cancer and serve as the basis for precise medicine with few or no side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 129 publications
1
13
0
Order By: Relevance
“…Adhesion molecules like L1CAM, which are involved in direct or indirect interactions between tumor cells and their microenvironment have been identified as potential targets for treatment of cancers [36,37], especially as L1CAM expression has been linked to augmented protection from apoptosis and increased chemoresistance in various cancer entities including retinoblastomas [21,23,38,39]. Besides, a multitude of studies showed that L1CAM is overexpressed in a variety of human cancers (for review see: [9]) and in nearly all cancers L1CAM expression was associated with poor prognosis, tumor progression and metastasis [9].…”
Section: Accepted Articlementioning
confidence: 99%
“…Adhesion molecules like L1CAM, which are involved in direct or indirect interactions between tumor cells and their microenvironment have been identified as potential targets for treatment of cancers [36,37], especially as L1CAM expression has been linked to augmented protection from apoptosis and increased chemoresistance in various cancer entities including retinoblastomas [21,23,38,39]. Besides, a multitude of studies showed that L1CAM is overexpressed in a variety of human cancers (for review see: [9]) and in nearly all cancers L1CAM expression was associated with poor prognosis, tumor progression and metastasis [9].…”
Section: Accepted Articlementioning
confidence: 99%
“…However, one major problem of cancer treatments, which also applies to BC, is the multidrug resistance coupled with the toxicity of some chemotherapeutics [25,26]. The emergence of drug resistance triggers the search for new drugs or drug adjuvants and, simultaneously, the need for a better understanding of the molecular mechanisms involved in drug resistance [27,28]. Accordingly, a search for compounds that are aimed at different therapeutic targets and/or that potentiate the existing established drugs with minimal, or at least decreased, toxicity towards normal cells has become a priority [29].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, chemotherapeutic resistance to ADM has emerged as one of the essential reasons for treatment failure and death associated with breast cancer [4,5]. Significant efforts should be undertaken to resolve the molecular mechanisms that lead to ADM resistance, and identified novel biomarkers that can predict treatment response and overcome ADM resistance Placenta-specific 8 (PLAC8, Onzin) was firstly identified via genome-wide gene expression analysis in the placenta, and PLAC8 protein was restricted to the spongiotrophoblast layer of the mouse placenta [6,7].…”
Section: Backgroudmentioning
confidence: 99%